ANTECEDENT OF FARMERS’ RESPONSE TO THE COCOA REHABILITATION PROGRAMME IN THE SEFWI-BOAKO COCOA DISTRICT, GHANA - Christian Yeboah Boateng; Maxwell Asiamah; Enoch Kwame Tham-Agyekum; Frederick Osei Tawiah; John-Eudes Andivi Bakang (Agricultural Socio-Economics Journal, 2023)
The paper assesses the antecedents of farmers' response to the cocoa rehabilitation program (CRP) in Sefwi-Boako District. The study adopted a quantitative method (descriptive survey design) to obtain 400 respondents through purposive and proportional sampling techniques. Face-to-face interviews with questionnaires were used to collect primary data from respondents. Descriptive (percentages, frequencies, mean, standard deviation) and inferential statistics (binary probit regression analysis) were used to analyze data. The results reveal that farmers had a neutral perception of the cocoa rehabilitation program and its effectiveness for cocoa production. Results from binary probit regression show that sex, educational level, cooperative membership, household size, and access to extension service were the significant factors determining farmers' participation in the cocoa rehabilitation program. The study contributes to the existing literature on the specific antecedents to farmer's participation in the Cocoa Rehabilitation Programme. If cocoa farmers are to respond to the program through participation, then these antecedents.